KOMPETENSI SOSIAL GURU DALAM PEMBELAJARAN DAN PENGEMBANGANNYA - Hasbi Ashsiddiqi (Ta'dib: Jurnal Pendidikan Islam, 2012)
Social competence of teachers is very supportive in the teaching and learning processes, both in the classroom and outside the classroom. One of the competences is social competence. A teacher must have a good social life in order to support the teaching and learning processes. Social competence means the ability and skill of a teacher with social intelligence to communicate and interact with others such as students effectively in the implementation of the teaching and learning processes. Social competence of teachers is really needed in the teaching and learning processes in order  to have teachers as a role model for students in developing students who possess personal conscience, care and empathy for others. Social competence of teachers can be developed through the increasing of social intelligence by joining in trainings related to social competence and adapting in place to work at.